Penyelesaian Sengketa Jual Beli Tanah Waris - Miftahuljannah Sidik; Nur M. Kasim; Sri Nanang Kamba (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Inherited land is very risky to be traded because the land is still in the name of the heir or a person who has died, while the heirs want the inherited land to be sold as soon as possible so that it can be divided among the heir's family. Ownership rights to the heir's inherited land completely belong to the heir who has a legal relationship with the heir. This type of research uses library research methods by studying scientific works related to the problem being studied. As well as normative legal research that studies data from legal provisions or regulations, newspapers, journals, and others. The results of this study indicate that the mediation process is very useful for resolving disputes over the sale and purchase of inherited land. In this case the mediator has an important role in resolving this problem by reconciling the parties.